2022
DOI: 10.1039/d2ra00809b
|View full text |Cite
|
Sign up to set email alerts
|

Emerging cold plasma treatment and machine learning prospects for seed priming: a step towards sustainable food production

Abstract: The perspective of machine learning for modeling plasma treatment parameters in agriculture for the development of synergistic protocols for different types of seed priming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 139 publications
1
34
0
Order By: Relevance
“…[ 39 ] Phytohormones are organic materials produced during plant metabolism, capable of regulating physiological responses to mediate plant growth and development. [ 70 ] Phytohormones determine the abilities of plant adaptation to abiotic stresses by modulating a range of stress‐adaptive responses [ 71 , 72 , 73 , 74 ] To date, there is limited information provided on how nanopriming modulates plant endogenous hormones to combat hostile environmental conditions. Herein, our results showed that PNC priming significantly increased shoot GA 3 and ABA contents by 31% and 149%, respectively, compared to NNP treatment under saline conditions (Figure 3a,b ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] Phytohormones are organic materials produced during plant metabolism, capable of regulating physiological responses to mediate plant growth and development. [ 70 ] Phytohormones determine the abilities of plant adaptation to abiotic stresses by modulating a range of stress‐adaptive responses [ 71 , 72 , 73 , 74 ] To date, there is limited information provided on how nanopriming modulates plant endogenous hormones to combat hostile environmental conditions. Herein, our results showed that PNC priming significantly increased shoot GA 3 and ABA contents by 31% and 149%, respectively, compared to NNP treatment under saline conditions (Figure 3a,b ).…”
Section: Discussionmentioning
confidence: 99%
“…To fulfill the needs of an ever-growing population, it is necessary to ensure a sufficient amount of high-quality raw materials. In this case, NTP is a suitable alternative to the already used technologies [ 102 , 103 , 104 ]. Plasma has been effectively used to decontaminate various food surfaces such as fruit, vegetables, and meat ( Table 2 ).…”
Section: Ntp Technology In the Management Of Fungal Contamination Dis...mentioning
confidence: 99%
“…resistant seeds can result in increased agricultural output ( Shelar et al., 2021 ). Seed priming is one of the prime approaches for maintaining cost-effectiveness, eco-friendly sustainable farming and offered different benefits including less amount of use of fertilizer and pesticides, high percentages of seed germination, and increased disease-resistant capacities in plants ( Shelar et al., 2022 ; Mitra et al., 2021 ; Acharya et al., 2020 ). Nanoparticle-based seed priming (soaking of seeds in nanomaterials) influences seed germination and promotes plant growth by exhibiting different types of mechanisms such as the creation of nanopores for enhanced water uptake, generation of hydroxyl radicals for cell wall loosening, up-regulation of aquaporin genes and rebooting ROS/antioxidant systems in germinating seeds, etc.…”
Section: Agricultural Application Of Nanobiosensormentioning
confidence: 99%